Serum Cytokine Production in Patients with Cutaneous Leishmaniasis Before and After Treatment (Iraqi Journal of Medical Sciences, 2016)
Background: Cutaneous leishmaniasis (CL) is caused by a protozoan from the genus Leishmania that infect macrophages of many mammals including humans, their infection induces both humoral and cellular immune responses, but the balance of their expression varies with the type of the disease.Objective: The aim of the present study is to understand the effect of antimonial compounds on some serum cytokines levels that include (IFN-?, TNF-?, TGF-?, IL-1?, IL-6, IL-8) before, during and after treatment from CL infection.Methods: Eighty people were included in the present study, 60 patients with CL lesions and 20 healthy individuals (control). Patients were diagnosed on the basis of clinical and parasitological criteria. All patients treated with pentostam by intralesional injection. Serum (IFN-?, TNF-?, TGF-?, IL-1?, IL-6, IL-8) levels were determined by ELISA using a quantitative sandwich enzyme immunoassay technique.Results: Serum levels of (TNF-?, IL-1?, IL-6, and IL-8) were significantly higher in patients group than healthy subjects (p < 0.05). INF-? and TGF-? levels were decreased significantly during infection with CL. During therapy with pentostam, cytokines levels (IFN-?, TNF-?, TGF-?, IL-1?, IL-6, IL-8) were significantly increased (p < 0.05). All cytokines levels returned to the normal values after three months of healing from CL lesions.Conclusions: Cytokines plays an important role in the resolution of CL infection. Pentavalent antimonials compounds may have immuno-stimulating effects which may be responsible for its antimicrobial activities.Key words: Cutaneous leishmaniasis, cytokines, treatment, pentostam.
Keywords: Cutaneous leishmaniasis; cytokines; treatment; pentostam